The Effect of Bisphosphonate Treatment on Blood Lipid Parameters in Patients with Postmenopausal Osteoporosis - Canan Tıkız; Fatma Taneli; Çiğdem Tüzün (Galenos Yayinevi, 2005)
Bisphosphonates are currently the most preferred class of drugs used for the treatment of metabolic bone disease such as osteoporosis and Paget's disease. Although their exact mechanism has not been identified, the compounds containing amino group (amino bisphosphonates) were shown to decrease osteoclast activation by inhibiting mevalonate pathway. Because mevalonate pathway is essential in production of cholesterol, these compounds could also interfere with cholesterol synthesis. In the present study, the effects of aminobisphosphonates on lipid parameters in subjects who were diagnosed as osteoporosis were investigated. For this reason, 50 postmenopausal osteoporotic subjects were included in the study and 25 of them (mean age:54±9 years) received alendronate sodium (70mg/week) and the remaining 25 subjects (mean age:55±8 years) were given risedronate sodium (35mg/week). Blood samples were analyzed at baseline and at the end of sixth months. Total cholesterol, high density cholesterol (HDL-chol), low density cholesterol (LDL-chol), triglyceride, apolipoprotein A (Apo-A), apolipoprotein B (Apo-B) and lipoprotein (a) (Lip a) were investigated as lipid parameters. Total alkaline phophatase (TAP), bone-specific alkaline phophatase (BAP), osteocalcine (OCL) and urine deoxyprydolin (DPD) levels were assessed as bone remodeling markers. After six month treatment period, while significant changes were observed in bone remodeling parameters (p<0.05), no significant changes were found in all measured lipid parameters (p>0.05). Our results suggest that moderate-term oral aminobisfosphonate treatment has no significant effect on blood lipid parameters.